Legal Analysis of the Concept and Provisions of "Unenforceable" Status in Iranian Commercial Law - Ahad Golizadeh Manghutay (پژوهش‌نامه حقوق اسلامی)
‌ ∴ Introduction ∴ ‌The Iranian Commercial Code, as originally enacted in 1932 (1311 SH) and subsequently amended in 1969 (1347 SH), draws heavily from the Napoleonic Code and remains largely devoid of Islamic jurisprudence influences. Notably, the term "Unenforceable" is absent from both versions of the code. Instead, the legal framework utilizes the concept of "Valid but Voidable" to describe transactions or actions that lack certain required conditions but are not outright invalid. These transactions can be remedied, preventing them from being declared voidable. This article seeks to explore the nuanced distinctions between "Valid," "Invalid," and "Valid but Voidable" statuses in the context of Iranian commercial law, particularly examining the concept of enforceability and its implications.‌ ∴ Research Question ∴ ‌The primary research question this article addresses is: How does the absence of the term "Unenforceable" in the Iranian Commercial Code affect the legal interpretation and status of transactions, particularly in relation to the concepts of "Valid but Voidable" and "Invalid"? Additionally, it investigates whether there is a legal basis for incorporating or substituting the concept of "Unenforceable" within the existing legislative framework.‌ ∴ Research Hypothesis ∴ ‌The hypothesis underlying this research posits that the determination of whether a transaction or action is "Valid," "Invalid," or "Valid but Voidable" under Iranian commercial law is significantly influenced by the scope of authority exercised by company representatives. It suggests that actions taken outside the scope of authority may render transactions voidable or invalid, but that the absence of an "Unenforceable" status creates ambiguity. Moreover, the research hypothesizes that it may be possible to conceptually replace or introduce the term "Unenforceable" within the current legal framework, particularly in situations where the legal status of transactions is otherwise indeterminate.‌ ∴ Methodology & Framework, if Applicable ∴ ‌This article adopts a doctrinal legal research methodology, focusing on a detailed analysis of primary legal texts, including the original 1932 Commercial Code and the 1969 Amended Act. The research involves a comparative study of the relevant provisions, considering both the original and amended texts, to understand the legislative intent and the practical implications of the existing terminology. The article also explores the potential for extending the current legal interpretations to cases where the enforceability of transactions is in doubt. Through this approach, the research aims to critically evaluate the possibility of integrating or substituting the "Unenforceable" status within the Iranian commercial law framework, offering a potential resolution to the ambiguities identified.‌ ∴ Results & Discussion ∴ ‌The analysis of the Iranian Commercial Code reveals a deliberate avoidance of the term "Unenforceable", opting instead for the concept of "Valid but Voidable" to describe transactions that, while lacking certain required conditions, are not entirely invalid. The research finds that this substitution has significant implications across various aspects of commercial law, not just within company law or the 1969 Amended Act but also within the broader scope of the original 1932 Code. The distinction between "Valid," "Invalid," and "Valid but Voidable" emerges as a central theme, with the latter effectively replacing the concept of unenforceability in cases where a legal or contractual deficiency exists.     The study identifies key areas where the "Valid but Voidable" status is applied, such as in transactions involving company representatives who act beyond their scope of authority, dealings with a bankrupt merchant's assets, and self-dealing transactions by corporate officers. It also highlights the doctrinal underpinnings of this substitution, rooted in principles of agency law, which emphasize the need to protect the interests of third parties and maintain the expediency of commercial transactions.     Furthermore, the research discusses the retroactive effect of voidability rulings, emphasizing that remedying the grounds for voidability before a court ruling can preserve the transaction’s validity. However, once a ruling is issued, its effects are generally binding on the parties involved but not on third parties who acted in good faith. This discussion extends to the principles of independence of signatures and the protection of good-faith holders, underscoring the complexities of enforceability in commercial transactions.‌ ∴ Conclusion ∴ ‌The research concludes that the Iranian Commercial Code's approach of substituting "Unenforceable" with "Valid but Voidable" provides a flexible yet robust framework for dealing with questionable transactions in commercial law. This substitution, while safeguarding the interests of involved parties, especially third parties, ensures that commercial transactions remain efficient and enforceable within the legal system. The principle of expediency, vital in the context of commercial law, supports this approach by allowing for remedial measures that can retroactively validate transactions before voidability rulings are issued.